(untitled) (Eurasian Medical Research Periodical, 2023)
The need to modernize (modernize) the primary medical and sanitary care service and switch to a new model (pattern) of patronage service arose because the system of visiting the homes of pregnant and giving birth women and young children did not sufficiently meet the modern quality requirements.